Activation of ethylene signaling pathways enhances disease resistance by regulating ROS and phytoalexin production in rice. (21st January 2017) - Yang, Chao; Li, Wen; Cao, Jidong; Meng, Fanwei; Yu, Yongqi; Huang, Junkai; Jiang, Lan; Liu, Muxing; Zhang, Zhengguang; Chen, Xuewei; Miyamoto, Koji; Yamane, Hisakazu; et al.
Summary: Ethylene plays diverse roles in plant growth, development and stress responses. However, the roles of ethylene signaling in immune responses remain largely unknown. In this study, we showed that the blast fungus Magnaporthe oryzae infection activated ethylene biosynthesis in rice. Resistant rice cultivars accumulated higher levels of ethylene than susceptible ones. Ethylene signaling components OsEIN2 and the downstream transcription factor OsEIL1 positively regulated disease resistance. Mutation of OsEIN2 led to enhanced disease susceptibility. Whole‐genome transcription analysis revealed that responsive genes of ethylene, jasmonates (JAs) and reactive oxygen species (ROS) signaling as well as phytoalexin biosynthesis genes were remarkably induced. Transcription of OsrbohA/B, which encode NADPH oxidases, and OsOPRs, the JA biosynthesis genes, were induced by M. oryzae infection. Furthermore, we demonstrated that OsEIL1 binds to the promoters of OsrbohA/OsrbohB and OsOPR4 to activate their expression. These data suggest that OsEIN2‐mediated OsrbohA/OsrbohB and OsOPR transcription may play essential roles in ROS generation, JA biosynthesis and the subsequent phytoalexin accumulation. Therefore, the involvement of ethylene signaling in disease resistance is probably by activation of ROS and phytoalexin production in rice during M. oryzae infection. Significance Statement: Ethylene plays diverse roles in plant growth, development and stress responses, but the roles of ethylene signalling in immune responses remain largely unknown. Here we used mutants or transgenic plants overexpressing an ethylene signalling membrane protein or a downstream transcription factor to clarify the roles of ethylene signalling in disease resistance. We found that infection with Magnaporthe oryzae activated ethylene biosynthesis and that elevated ethylene levels enhanced disease resistance by facilitating ROS and phytoalexin production in rice.